Factors influencing adoption of e-services in rural India – perspectives of consumers and service providers. Issue 2 (14th June 2019) - Ray, Arghya; Bala, Pradip Kumar; Dasgupta, Shilpee A.; Sivasankaran, Narayanasamy
Abstract : Purpose: This paper aims to explore the consumers' and service-providers' perspectives on the factors influencing adoption of e-services in rural India. The purpose is to enable better diffusion of technology for societal development in this digital era. Design/methodology/approach: Using qualitative-based multiple-participant interviews, this study explores the factors affecting e-service adoption from two different perspectives. While interviews were conducted in five villages with 14 respondents to find out the perspectives of the consumers, this study also explores the service-providers' perspectives through interviews conducted among 11 managerial respondents. Findings: Catering to personal needs, improving perceived usefulness, value-added options, data analytics for better understanding customers and improving service delivery of the e-service are the major factors identified by the service-providers. The study also concludes that convenience, compatibility, societal influence and availability of value-added addition of the e-service are decisive in e-service adoption from the perspectives of the consumers. Research limitations/implications: The first limitation of this research is that there can be common method bias. Second, there were overlapping themes. Practical implications: This study can help researchers working on the adoption of e-services in under-developed/developing countries. The findings of this study may help industries to focus on the determinants while designing the e-services for improving their rate of adoption. Social implications: This study will help in better diffusion of e-services in rural areas, which in turn will help in societal development in this digital era. Originality/value: The focus is on societal development through the adoption of e-services in rural areas. To the best of the knowledge of the researchers, no qualitative study has been performed to capture the perspectives of both the service-providers and the consumers on the adoption of e-services in India.